2011
DOI: 10.1016/j.radmeas.2010.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability of infrared stimulated luminescence of sedimentary K-feldspar

Abstract: The thermal stability of the infrared stimulated luminescence (IRSL) signal measured at 50 °C as a function of IR stimulation time was investigated using KF grains extracted from sediments from central China. A dependence of thermal stability of IRSL signal on IR stimulation time and stimulation temperature were observed in pulse annealing studies. Relatively lower thermal stability is given by the initial part of the IRSL measured at 50 °C, than the later part of IRSL curve. Based on these observations, the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 22 publications
3
21
0
Order By: Relevance
“…6a that the residual signals measured at higher temperatures are more thermally stable than those measured at lower temperatures: for example, the residual signal stimulated at 100°C starts to decrease from an annealing temperature of 350°C, whereas the 250 and 300°C residual signals are stable up to an annealing temperature of almost 400°C although the residual signal at 300°C appears to decrease at a slightly lower temperature than 200°C signal. A similar trend was observed by Li and Li (2011b) for the total MET-pIRIR signals of a sand dune sample from China, but the pulse annealing curves for the total MET-pIRIR signals from the same set of aliquots of sample LC10-07 exhibit a different pattern. As shown in Fig.…”
Section: Thermal Stability Of the Met-pirir Trapssupporting
confidence: 79%
“…6a that the residual signals measured at higher temperatures are more thermally stable than those measured at lower temperatures: for example, the residual signal stimulated at 100°C starts to decrease from an annealing temperature of 350°C, whereas the 250 and 300°C residual signals are stable up to an annealing temperature of almost 400°C although the residual signal at 300°C appears to decrease at a slightly lower temperature than 200°C signal. A similar trend was observed by Li and Li (2011b) for the total MET-pIRIR signals of a sand dune sample from China, but the pulse annealing curves for the total MET-pIRIR signals from the same set of aliquots of sample LC10-07 exhibit a different pattern. As shown in Fig.…”
Section: Thermal Stability Of the Met-pirir Trapssupporting
confidence: 79%
“…Based on the reduction of TL from IR bleaching, they suggested that the IRSL traps of their K-feldspar sample mainly originated from deep traps associated with the ~410°C TL peak. In a later study on the effect of IR bleaching on the TL of Kfeldspar from sediments from North China, Li and Li (2011b) found that the IRSL are associated with the 350 and 400°C TL peaks, which led them to suggest that at least two groups of traps (shallow and deep) are associated with the IRSL signals. All these studies suggest that the IRSL signal from K-feldspar is thermally stable over the datable period (e.g., <1 Ma).…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…The thermal stability of the pIRIR signal was investigated in several studies (Li and Li, 2011b;Thomsen et al, 2011;Fu et al, 2012b;. Based on a pulse anneal study of the IRSL and pIRIR signals on the K-feldspar grains from several sedimentary samples, Thomsen et al (2011) showed that the pIRIR signal has a greater thermal stability than the 50°C IRSL signal (e.g., heating to ~400°C can erase most of the 50°C IRSL signal, whereas the pIRIR(50,290) signal is still not completely erased by heating to ~550°C).…”
Section: Thermal Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the pIRIR and the MET-pIRIR signals from feldspars have been found to be thermally stable up to 400 °C in pulse annealing tests (e.g. Li and Li, 2011b;Thomsen et al, 2011), suggesting that these signals are more thermally stable than the quartz OSL. It is thus expected that the closure temperature of feldspar IRSL is higher than that of quartz OSL.…”
Section: Discussionmentioning
confidence: 99%